Optimal nonlinear polynomial control of a quarter-vehicle suspension system under harmonic and random road excitations - Xudong Gu; Bingxin Zhao; Yuhao Liu (Journal of Low Frequency Noise, Vibration and Active Control, 2024)
The present paper proposes an optimal polynomial control strategy for a quarter-vehicle suspension system based on dynamic programming. The optimal control objective is to decrease the responses of sprung mass acceleration, suspension deformation and road excitation, which are reflected in the performance index. The optimal control force is obtained through the principle of dynamic programming, and the form of the optimal control force mainly depends on the form of the cost function. The optimal nonlinear polynomial control (NPC) force is derived by selecting the cost function in polynomial form. The linear feedback matrix and nonlinear feedback matrix in the NPC force are determined by the Riccati equation and Lyapunov equation, respectively. The root mean square (RMS) responses of the sprung mass acceleration, suspension deformation and road load of driving vehicles under deterministic and random road surfaces are calculated. The numerical results showed that the proposed NPC strategy has a better control effect over the traditional linear quadratic regulator (LQR), especially on the peak reduction of sprung mass acceleration. Finally, the optimal control force is divided into active control force and passive control force. The energy input of the optimal control force can be reduced by only inputting the active control force.